2004
DOI: 10.1096/fj.04-1855fje
|View full text |Cite
|
Sign up to set email alerts
|

Migration of antigen presenting cells from periphery to the peritoneum during an inflammatory response: role of chemokines and cytokines

Abstract: We demonstrate the migration of antigen presenting cells (APCs), macrophages, and dendritic cells from the subcutaneous site to the peritoneum after they have picked up the antigen, using cell tracking dye. The migration of the APCs is more universal as it was also observed after injection of MethA tumor, DH-5alpha cells, and leishmania parasites, in addition to AK-5 tumor cells. Cellular migration is mediated by several chemokines and cytokines that also induce heavy influx of immune cells into the peritoneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The use of fluorescent microspheres to track endogeneous APCs has been commonly used to analyze the migratory behavior of DCs in other tissues than the CNS [1], [12]. In our experimental settings, however, one has to consider that microspheres may not have been exclusively taken up by CSF-circulating APCs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fluorescent microspheres to track endogeneous APCs has been commonly used to analyze the migratory behavior of DCs in other tissues than the CNS [1], [12]. In our experimental settings, however, one has to consider that microspheres may not have been exclusively taken up by CSF-circulating APCs.…”
Section: Discussionmentioning
confidence: 99%
“…administration can be considered as a suitable route for vaccination because the antigen will generate its own set of regulatory T cells (13). The peritoneum is an important lymphoid organ, where antigen presentation to immune cells takes place (12,26). Studies on the effect of the immunization route on the type of elicited immune response (Th1 or Th2) have shown that immunization via the i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra et al . [31] demonstrated that macrophages migrated to regional lymph nodes and the peritoneum after ingesting antigens from regressive tumour tissue. In the peritoneal cavity, these cells become activated.…”
Section: Discussionmentioning
confidence: 99%